2019
DOI: 10.1111/iej.13115
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam computed tomography in Endodontics – a review of the literature

Abstract: The use of cone beam computed tomography (CBCT) in the diagnosis and/or management of endodontic problems is increasing and is reflected in the exponential rise in publications on this topic in the last two decades. The aim of this paper is to: (i) Review current literature on the endodontic applications of CBCT; (ii) Based on current evidence make recommendations for the use of CBCT in Endodontics; (iii) Highlight the areas in which more research is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
191
0
26

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(220 citation statements)
references
References 133 publications
(237 reference statements)
3
191
0
26
Order By: Relevance
“…A CBCT examination should only be considered after a detailed clinical examination, including conventional radiographs, has been performed (Kruse et al , Patel et al a). The potential benefits as well as potential risks must be discussed with the patient beforehand.…”
Section: Criteria For Use Of Cbct In Endodonticsmentioning
confidence: 99%
“…A CBCT examination should only be considered after a detailed clinical examination, including conventional radiographs, has been performed (Kruse et al , Patel et al a). The potential benefits as well as potential risks must be discussed with the patient beforehand.…”
Section: Criteria For Use Of Cbct In Endodonticsmentioning
confidence: 99%
“…2 CBCT produces undistorted three-dimensional images of the maxillofacial skeleton, including the teeth and the surrounding tissues, with a relatively lower effective radiation dose than that of computed tomography. 3 CBCT is therefore considered a valuable tool for detecting MB2 canals and could be used in the endodontic treatment of MFMs. 4,5 In recent years, many studies have assessed the prevalence of the MB2 canal, most of which used CBCT, as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…La TCHC sólo debería estar reservado para casos en los que exista un beneficio potencial de una evaluación tridimensional. Es esencial que la exposición a la radiación del paciente se mantenga tan baja como sea razonablemente posible (ALARA) (26). En el presente estudio se utilizó un FOV de campo amplio para poder evaluar ambos maxilares con todas las piezas dentarias, en casos como lesiones periapicales, evaluación de resultado de tratamiento de conducto, fracturas verticales, evaluación de anatomía del conducto radicular, evaluación pre-quirúrigca, diagnóstico y manejo de reabsorción radicular se optará por un FOV de campo pequeño (18).…”
Section: Discussionunclassified